Locally Advanced Prostate Cancer at High Risk of Progression: A Treatment Strategy, A Review of Clinical Studies - M. S. Salomov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The clinician doctors should be decided the difficult task of determining the exact stage of prostate cancer. This concerns, first of all, stage T3 - or locally progressive, the presence of which indicates that the tumor is spreading beyond the capsule. Prostate cancer is the most common solid tumor in Europe, with an incidence rate of 214 cases per 1,000 men, which is higher than for lung and colorectal cancers [3]. In 2013, prostate cancer ranked 3rd in the structure of oncological diseases in men in Russia, 29,158 new cases of the disease were recorded, 9,535 patients died from prostate cancer. Over the past 5 years, the number of patients with PCa in our country has increased, in particular, in 2015 - 372, in 2016 - 443, in 2019 the number of patients reached 483 (an increase of 23%). There is also an increase in the incidence, which in 2015 amounted to 1.2 patients per 100 thousand of the population, in 2019 this figure was 1.5. (Tillyashaikhov M.N. et al., 2020). The optimal therapy for patients with clinically locally progressive prostate cancer has not been finally determined, and the tactics of treating these patients cause a lively discussion. Many controversial issues regarding the choice of a particular method remain unresolved.